Le rôle de l’enseignant dans la construction de contenus en situation de débats philosophiques ou disciplinaires - Audrey Destailleur (Recherches en Éducation)
This article realize a doctoral research based on the observation of debates at school in several disciplines: philosophy, literary and sciences. Starting from a didactic and comparative analysis, we would like to emphasise in particular specificities of the organisation of debates by teachers in philosophical debates at school. The analysis composed of the transcripts from the wiretaps of three series of debates led by four teachers in philosophy, literary and sciences, like to point out teachers’s choice on singular performing of phylosophical debate and describe the discursive organization of debate by teacher on the basis of the analysis of teachers’s scaffolding.